Mesoscale atmospheric processes over an Arctic fjord as observed during a research aircraft campaign in winter - Suomi, Irene; Vihma, Timo; Nygård, Tiina; Hartmann, Jörg; Lüpkes, Christof (Polar research, 2025)
Unique research aircraft observations were conducted within an Arctic fjord in Svalbard during three days in March 2013. Wijdefjorden is 110 km long, 5–15 km wide and has a north–south axis. Two-thirds of the fjord were covered by land-fast sea ice, but the northern part of the fjord was open. On two days the flow over the fjord was largely controlled by orographic channelling of the north-easterly wind, and on all three days a cold-air mass accumulated over the sea ice in the fjord and gradually propagated towards the open sea in the north. An ice breeze (analogous to land breeze) circulation, due to a strong temperature gradient across the sea-ice edge, was a key driver of the southerly near-surface wind over the fjord. On two days, the cold-air mass reached the open sea and the near-surface air mass warmed rapidly by several Kelvins. On one day, the channelled northerly flow pushed the cold-air mass to the south, from where it gradually propagated back to the north after the channelled flow had weakened. The results suggest that the channelling of the large-scale flow in the fjord can suppress the ice breeze to a shallow near-surface layer and even push the cold-air mass far south of ice edge. The near-surface air temperature and wind fields that were based on the Copernicus Climate Change Service Arctic Regional Reanalysis (CARRA) data set included large errors because CARRA did not have any sea ice in the fjord.